Cselp functions as the nuclear export receptor for importin α in yeast - Künzler, Markus; Hurt, Ed (FEBS letters, 1998)
CSE1 is essential for yeast cell viability and has been implicated in chromosome segregation. Based on its sequence similarity, Cse1p has been grouped into the family of importin β-like nucleocytoplasmic transport receptors with highest homology to the recently identified human nuclear export receptor for importin α, CAS. We demonstrate here that Cse1p physically interacts with yeast Ran and yeast importin α (Srp1p) in the yeast two-hybrid system and that recombinant Cse1p, Srp1p and Ran-GTP form a trimeric complex in vitro. Re-export of Srp1p from the nucleus into the cytoplasm and nuclear uptake of a reporter protein containing a classical NLS are inhibited in a cse1 mutant strain. These findings suggest that Cse1p is the exportin of importin α in yeast.